Latin Political Propaganda in the War of the Spanish Succession and Its Aftermath, 1700-1740. - MIRALLES, EULÀLIA (Scripta)
The article focuses on the work "Latin Political Propaganda in the War of the Spanish Succession and Its Aftermath, 1700-1740" by Alejandro Coroleu, which explores the importance of political propaganda in Latin during the War of the Spanish Succession. Coroleu argues that the political literature of this conflict, beyond its military dimension, played a crucial role in legitimizing the claimants to the throne and in the dissemination of ideas through various literary genres. The work is structured into four chapters that address topics such as dynastic legitimization, war propaganda, and literary production in the context of the court, the church, and academia. Additionally, it includes unpublished texts and an analysis of how Latin propaganda was used to communicate and justify the actions of the actors involved in the conflict.